To solve the expression \(-3^0 + 4.5\), we need to follow the correct order of operations while properly interpreting the expression.
- Calculate \(3^0\): Any non-zero number raised to the power of 0 is 1. Thus, \(3^0 = 1\).
- Then apply the negative sign: So, \(-3^0 = -1\).
- Now substitute back into the expression: \(-3^0 + 4.5 = -1 + 4.5\).
- Finally, perform the addition: \(-1 + 4.5 = 3.5\).
Thus, the correct process and result is:
\(-3^0 + 4.5 = -1 \cdot 3^0 + 4.5 = -1 \cdot 1 + 4.5 = -1 + 4.5 = 3.5\).
The fourth response correctly represents this process.